Ectopic fat in liver and skeletal muscle is associated with shorter overall survival in patients with colorectal liver metastases. Issue 4 (1st June 2021) - van Dijk, David P.J.; Zhao, Junfang; Kemter, Katrin; Baracos, Vickie E.; Dejong, Cornelis H.C.; Rensen, Sander S.; Olde Damink, Steven W.M.
Abstract: Background: Myosteatosis has been associated with shorter overall survival in cancer patients. The increase in ectopic fat might not be limited to skeletal muscle only and might also extend to other sites such as the liver, resulting in non‐alcoholic fatty liver disease (NAFLD). In this study, we assessed the relationship between myosteatosis and NAFLD and their association with overall survival in patients with colorectal liver metastases undergoing partial hepatectomy. Methods: Patients were selected from a prospective cohort of 289 consecutive patients with colorectal liver metastases. All patients with a preoperative computed tomography (CT)‐scan and liver biopsy obtained during surgery were included. If available a second pre‐operative CT scan was used to calculate changes in body composition over time. Muscle radiation attenuation was defined as the average Hounsfield units on CT of all muscle tissue at the L3 level. Liver biopsies were graded by a liver pathologist using the steatosis, activity, and fibrosis scoring system for NAFLD. Results: Two‐hundred and eighteen patients had an available liver biopsy of which 131 patients had two available pre‐operative CT scans with an average time interval of 3.2 months. One‐hundred and thirty‐five (62%) biopsies were classified as NAFLD. In multivariable Cox‐regression analysis, NAFLD [hazard ratio (HR): 1.8, 95%‐confidence interval (CI) 1.0–3.0, P  = 0.037], increase in myosteatosis (HR 1.8, 95%‐CI 1.1–2.9, P  = 0.018), and skeletal muscle loss (HR 1.7, 95%‐CI 1.0–2.9, P  = 0.035) were independently associated with shorter overall survival while high visceral adipose tissue fat content was associated with longer overall survival (HR: 0.7, 95%‐CI 0.5–0.9, P  = 0.014). Conclusions: Ectopic fat content of liver as well as skeletal muscle tissue is independently associated with shorter overall survival in patients with colorectal liver metastases, while increased visceral adipose tissue fat content is associated with longer overall survival.